First trimester fetal heart rate as a predictor of newborn sex*. (3rd March 2016) - Bracero, L. A.; Seybold, D. J.; Witsberger, S.; Rincon, L.; Modak, A.; Baxi, L. V.
Abstract: Objective : To predict the sex of newborns using first trimester fetal heart rate (FHR). Methods : This was a retrospective review of medical records and ultrasounds performed between 8 and 13 weeks of gestation. Continuous variables were compared using Student's t -tests while categorical variables were compared using Chi-square test. Results : We found no significant differences between 332 (50.7%) female and 323 (49.3%) male FHRs during the first trimester. The mean FHR for female fetuses was 167.0 ± 9.1 bpm and for male fetuses 167.3 ± 10.1 bpm ( p = 0.62). There was no significant difference in crown rump length between female and male fetuses (4.01 ± 1.7 versus 3.98 ± 1.7 cm; p = 0.78) or in gestational age at birth (38.01 ± 2.1 versus 38.08 ± 2.1 weeks; p = 0.67). The males were significantly heavier than females (3305.3 ± 568.3 versus 3127.5 ± 579.8 g; p < 0.0001) but there were no differences in the proportion of small for gestational age (SGA), average for gestational age (AGA) and large for gestational age (LGA) infants. Conclusions : We found no significant difference between the female and male FHR during the first trimester in contrast to the prevailing lay view of females having a faster FHR. The only statistically significant difference was that males weighed more than female newborns.